Effects of Aqueous Extract of Moringa olifera Leaves on Arsenic Trioxide Induced Hepato- Toxicity in Adult WistarRats (Sokoto Journal of Medical Laboratory Science)
Arsenic trioxide is an amphoteric oxide with highly toxic potential when inhaled or ingested. The potential effect of Moringa olifera (M. olifera) as a chelating agent of plant origin has not been determined hence the present study. Arsenic intoxication was induced by oral administration of arsenic trioxide to the rats. Thirty (30) rats weighing within the range of 250g-300g were randomly divided into groups (A, B, C, D, E, F) of five per group. Group A was the control being orally administered Iml of distilled water, Group B was orally administered 10mg/kg body weight of arsenic trioxide only, Groups C, D and E were orally administered graded doses of aqueous Moringa olifera leaves extract of 200mg/kg, 400mg/kg and 800mg/kg respectively and 10mg/kg body weight of arsenic trioxide, Group F was orally administered 800mg/kg body weight of aqueous Moringa olifera leaves extract only, for a period of twenty-eight (28) days with an orogastric tube. Thereafter, we studied the effects of arsenic trioxide on liver function enzymes, haematological parameters and liver histomorphology. In the group administered with arsenic trioxide only, there was a significant increase (p<0.05) in serum alanine transferase (ALT). Histological slides of caffeine intoxicated rats showed hepatic portal congestion, zonal necrosis, and periportal infiltrates of inflammatory cells). Moringa olifera extract at a high dose of 800mg/kg body weight was able to restore the levels of these parameters to normal. These findings therefore prove that high dose of M. olifera leaf extract was effective in reducing the resultant effects produced in the arsenic trioxide induced liver damage.